Detección de Leptospira spp. porcina en el centro de faenamiento del cantón Catamayo de la provincia de Loja - Eras Jaramillo, Estefany Mercedes (2023)
Leptospirosis is a widely distributed zoonosis of bacterial origin; this disease affects some animal species, such as pigs, causing reproductive alterations such as abortions, mummified piglets, stillbirths, and weak piglets, in Latin America; this zoonosis is 100 times more common than in other parts of the world. However, in Ecuador, few studies allow us to know the epidemiology of leptospirosis in animals, particularly in pigs, so this study had the following objectives: 1) To identify the presence of antibodies against Leptospira spp. in pigs slaughtered in the Catamayo canton of Loja province; 2) To identify pathogenic Leptospira in urine of pigs slaughtered in the Catamayo canton of Loja province and 3) To determine the factors associated with leptospirosis in pigs slaughtered in the Catamayo canton of Loja province, for this purpose, we collected information at the slaughtering center regarding breed, age, sex, and origin, in addition, we collected 100 urine and blood samples from pigs older than four months, to diagnose leptospirosis employing MAT (microscopic agglutination) and conventional PCR (hap1 gene), we estimated that 17 % of animals had antibodies against Leptospira spp.; the animals were seropositive to six serovars: Australis, Canicola, Sejroe, Pomona, Wolffi, and Autumnalis; 4 % of pigs slaughtered were positive in PCR. As for the associated factors, we obtained no statistically significant values. The results obtained in this investigation will serve as reference data for the epidemiology of the disease in this species in Ecuador. Keywords: Leptospirosis, pigs, MAT, PCR, Ecuador